Pengaruh Kualitas Pelayanan Terhadap Kepuasan Mahasiswa Program Studi Manajemen Fakultas Ekonomi Dan Bisnis Universitas Muhammadiyah Surakarta - Ansal, Arifin Putera; , Imronudin, SE,MSi,Ph.D (2016)
The objective of the research is to identify whether the service quality (tangible, reliability, responsiveness, empathy and assurance) has influence towards students' satisfaction. The population of the research is all of the students in Management Department Economic and Business Faculty Muhammadiyah University Surakarta. The writer uses convenience sampling as the sampling technique and takes 73 samples as respondents. The result of the research shows there is significancy relation between independent variable is quality of service to dependent variable. It is students' satisfaction. Value of responsiveness coefficient is variable which gives higher influence on students' satisfication than tangible, reliability, emphaty, and assurance variable. T-test gets that variable of service quality (tangible, reliability, responsiveness, emphaty, and assurance) have significancy influence on students' satisfaction. F-test shows that quality of service (tangible, reliability, emphaty, and assurance) collectively same have positive influence on students' satisfaction. Determining coefficient test of students' satisfaction is influenced by variable of service quality (tangible, reliability, responsiveness, emphaty, and assurance).